A case report on Spontaneous Abdominal Wall Endometriosis (Bangladesh Critical Care Journal, 2023)
Endometriosis is the presence of endometrial glands and stroma outside the uterus. Endometriosis is the commonestgynaecological problem; it affects 7 to 10% women in reproductive age group. Spontaneous abdominal wallendometriosis (AWE) is any ectopic endometrium found superficial to the peritoneum without the presence of anyprevious scar. In our case study, though the patient had a caesarean section, the endometriosis developed in unscarredarea. It was located below the umbilicus in the midline, which is a common site for spontaneous abdominalendometriomas. Initially the patient had cyclic infra-umbilical pain, gradually it became constant and severe. Due toirregular follow up and unusual site and presentation of the lesion, it took a long time to diagnose the condition. Duringoperation the mass was spotted in the midline and extend up to the peritoneum. It was taken out by wide local excision.Pathology revealed endometrial glands surrounded by a disintegrating mantle of endometrial stroma and fibrous scartissue in which there was a scattering of leucocytes. Spontaneous AWE is rare, accounting for 20% of all AWEs.Spontaneous endometriomas are usually diagnosed by pathology and the treatment of choice is surgical excisionBangladesh Crit Care J March 2023; 11 (1): 51-53